2012
DOI: 10.1051/0004-6361/201117133
|View full text |Cite
|
Sign up to set email alerts
|

Lithium abundances of nearby young solar-type stars based on optical high-resolution spectroscopy

Abstract: Context. Lithium has long been recognized as a powerful tool for investigating the internal mixing of low-mass stars. In addition, accurate measurements of lithium abundances in young solar-type stars provide independent and reliable age diagnostics. Aims. To study the relationship between lithium and activity in normal solar type-type stars and determine the effectiveness of lithium and kinematics as activity indicators, we perform a lithium survey of nearby late-type stars. We search for nearby young solar-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The W velocity is matched to a few MGs, however, both the U and V are at least ∼ 15 km s −1 from any MG.Target P -Using Li, an age of 30 − 150 Myr was estimated and Hα measurements suggest an age of 65 − 125 Myr. It has a U, V and W velocity at least 10 km s −1 from any MG Xing & Xing (2012). include this target as a young K4V object (we calculate K5) with a Li EW of 17 m Å which is almost 150 m Å lower than the measurement in this work.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The W velocity is matched to a few MGs, however, both the U and V are at least ∼ 15 km s −1 from any MG.Target P -Using Li, an age of 30 − 150 Myr was estimated and Hα measurements suggest an age of 65 − 125 Myr. It has a U, V and W velocity at least 10 km s −1 from any MG Xing & Xing (2012). include this target as a young K4V object (we calculate K5) with a Li EW of 17 m Å which is almost 150 m Å lower than the measurement in this work.…”
mentioning
confidence: 77%
“…It has a U, V and W velocity at least 10 km s −1 from any MG. Xing & Xing (2012) include this target as a young K4V object (we calculate K5) with a Li EW of 17 mÅ which is almost 150 mÅ lower than the measurement in this work. It is listed as a possible visual binary in Makarov (2003), however, two consistent RV measurements in this analysis suggest the object is not a close binary.…”
Section: Individual Objects Not Linked To Any Mgmentioning
confidence: 91%
“…It is J03332+462 (M0.0 V, pEW(Hα) = -3.4 +0.5 −0.3 Å, V577 Per B), a confirmed member of the ∼70 Ma-old AB Doradus moving group da Silva et al 2009;Schlieder et al 2012a). Its relatively bright primary at about 9 arcsec is a young K2 V star with strong ultraviolet and X-ray emission and lithium in absorption (Pounds et al 1993;Jeffries 1995;Montes et al 2001;Xing & Xing 2012). …”
Section: Hα Emissionmentioning
confidence: 99%
“…More recently, Xing (2010) derived a spectral type of K0 and measured the Li equivalent width of only 39 mÅ. In addition, Xing & Xing (2012) detected Hα in absorption, and Rebull et al (2010) found no significant infrared excess for this source based on Spitzer photometry. Altogether, these properties are consistent with V1110Tau being a young foreground dwarf not related to the Taurus population of YSOs (see also Briceno et al 1997).…”
Section: V1110taumentioning
confidence: 99%